Modelling industry specific policy with TIM: Treasury's multi-sector dynamic general equilibrium model of the Australian economy - Freya Carlton; Linus Gustafsson; Melissa Hinson; Jack Jaensch; Michael A. Kouparitsas; Niall Peat; Ken Quach; Sebastian Wende; Phillipp Womack (The Australian Government, The Treasury, 2023)
The Australian economy is constantly affected by technological, demand and policy shocks from home and abroad. The opportunities and challenges presented by these shocks create demand for government advice on the likely effects on households, firms and the Australian economy, and in turn appropriate policy responses. Treasury has developed a multisector dynamic generally equilibrium model to meet this need - the Treasury Industry Model (TIM). As a general equilibrium model, TIM captures the economy's interconnectedness and rich industry detail, enabling the net effects of policy or other exogenous changes to the economy to be assessed. TIM extends previous Australian models by incorporating forward-looking agents that are able to respond rationally to policy and technological changes, a well-defined balanced growth path defined endogenously, and a model-consistent welfare measure. These features, combined with TIM's significant production and industry detail, position the model well for informing advice on a range of industry- and trade-related policy questions.
Keywords: C68; D58; E13; E23; E60; H30; 330; many sector modelling; CGE modelling; industry policy analysis; general equilibrium